A physicalist rejoinder to some problems with omniscience; Or, how god could know what we know - Beyer, Jason A. (Sophia, 2004)
A certain objection to belief in God is based on the intrinsic incoherence of the concept of Divine Being or God. In particular, it questions the major traditional characteristic, notably omniscience, and its relation to omnipotence, moral unassailability, and absence of embodiment on the part of the Divine Being. In this paper, an attempt is made to counter this objection by an appeal, not to natural theology, but rather to physicalism in its application to human beings, and by extension to the possible consistency of God’s omniscience with the other divine attributes, which philosophers such as Michael Martin have found to be mutually inconsistent and therefore wanting.